The success factors of Bumiputra small and medium enterprise entrepreneurs in Alor Gajah / Mohd Azmil Alias - Alias, Mohd Azmil (Faculty of Business and Management, 2007)
Entrepreneurship creates wealth and reduces unemployment. Entrepreneurs contribute to industrialization as well as to economic growth; they improve living standards and tax revenues from their enterprises contribute to a nation's treasury. Not surprisingly, then, governments have been spending considerable sums of money trying to create entrepreneurs. The question remains, however, "can entrepreneurship really be taught?" To provide a response of any value, one must address the definition of entrepreneurship. As evident from the literature, there is no universally-accepted definition of entrepreneurs or of entrepreneurship. If entrepreneurship is equated with the causing of economic disequilibrium - as per the Schumpeterian literature - then one can argue that entrepreneurs tend to be born, rather than made. There were several factors that can lead to the success of the Bumiputra SME entrepreneurs. The research objectives of this study are what factors contribute to the success of Bumiputra SME entrepreneurs, is there any relationship between entrepreneurial traits and successful entrepreneurs and is there any relationship between managerial skills and successful entrepreneurs. The research objectives are to determine factors contribute to the success of Bumiputra SME entrepreneurs, to identify the relationship between entrepreneurial traits and successful entrepreneurs and to examine the relationship between managerial skills and successful entrepreneurs. In this research, it used simple random sampling, 60 respondents answering the questionnaire and using SPSS to process the data. As a result, it can be seen that universities and colleges and school and education system have significant relationship with the successful entrepreneurs.